1997
DOI: 10.1002/(sici)1097-0282(1997)44:4<323::aid-bip2>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the design of DNA sequence-specific lexitropsins

Abstract: Sequence‐specific polyamides that bind in the minor groove of DNA are attractive candidates for antibiotics, cancer chemotherapeutics, and transcriptional antagonists. This paper reviews the progress of structure‐based design of minor‐groove‐binding polyamides, from the first structure of netropsin with DNA, to the effective linked polyamides currently under study. A theory of polyamide specificity is also reviewed, introducing methods to determine the optimal strategies for targeting a given DNA sequence with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Binding affinities of hairpins containing hydroxypyrrole vary considerably based on the position of the hydroxypyrrole ring within the hairpin motif (24). Calculation of relative binding affinities of imidazole and hydroxypyrrole rings by Goodsell and coworkers (45) indicates that the hydroxypyrrole ring binds with a lower affinity for AT base pairs compared with the affinity of the imidazole ring for GC pairs. In the present study, the specificity for adenine observed with thiazole in the terminal position is comparable with the specificity for thymine provided by a hydroxybenzamide͞pyrrole pair in eight ring hairpin polyamides (44).…”
Section: Discussionmentioning
confidence: 99%
“…Binding affinities of hairpins containing hydroxypyrrole vary considerably based on the position of the hydroxypyrrole ring within the hairpin motif (24). Calculation of relative binding affinities of imidazole and hydroxypyrrole rings by Goodsell and coworkers (45) indicates that the hydroxypyrrole ring binds with a lower affinity for AT base pairs compared with the affinity of the imidazole ring for GC pairs. In the present study, the specificity for adenine observed with thiazole in the terminal position is comparable with the specificity for thymine provided by a hydroxybenzamide͞pyrrole pair in eight ring hairpin polyamides (44).…”
Section: Discussionmentioning
confidence: 99%
“…1, produced by Streptomyces netropsis [14], is one of the best-studied A-T rich DNA minor groove binders [15] which has been used in the development of antitumor drugs such as the lexitropsins [16,17]. Netropsin contains a core structure that is composed of a chain of two subsequently attached 5-acetamidino-N-methylpyrrol rings which is tailed by positively charged amidinium and guanidinium group-containing moieties that contribute a total of 2+ charges to the molecule, Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis and testing of analogues of netropsin and distamycin is a subject of active research [3][4][5]. It is hoped that by understanding the processes involved in the recognition of defined DNA base sequences, rational modifications of the basic molecular structure can be engineered to modulate both binding affinity and site selectivity for therapeutic gain.…”
Section: Introductionmentioning
confidence: 99%